A comparison of three methods used for determining chloride in acid copper sulfate plating bath / Gan Yen Shing - Gan, Yen Shing (2014)
Monitoring of chloride concentration in acid copper suflate plating bath is vital due to its important role in the quality of copper deposition. In this study, three different analytical methods which include potentiometric titration, UV-Vis spectroscopy and ion chromatography were used to determine the chloride in an actual acid copper sulfate plating bath to investigate their respective analytical performances. From the Oneway Anova and Tukey-Kramer test conducted, it can be concluded that the results from these three methods are significant different, with ion chromatography method showing the greatest difference compared to the other two methods. Besides this, it is determined that potentiometric titration method has an excellent precision and accuracy, UV-Vis method is quite precise but less accurate, and IC method is the least precise and accurate. Taking account of other factors such as skill required, reagents required, sample preparation time, analysis time, cost per sample, maintenance cost and others, potentiometric titration method is the most ideal method to be used.